Florid Foreign Body-type Giant Cell Response to Keratin Is Associated With Improved Overall Survival in Patients Receiving Preoperative Therapy for Esophageal Squamous Cell Carcinoma. (December 2021) - Chen, Wei; Zhao, Lei; Agoston, Agoston; White, Abby; Mazzola, Emanuele; Boyle, Patrick J.; Deshpande, Vikram; Hornick, Jason L.; Bueno, Raphael; Bass, Adam J.; Enzinger, Peter; Mamon, Harvey; et al.
Abstract : While most resection specimens from patients with neoadjuvantly treated esophageal squamous cell carcinoma show therapy-related changes in the form of inflammation and fibrosis, others harbor a florid foreign body-type giant cell response to keratin debris. The purpose of our study was to perform a detailed clinicopathologic analysis of these histologic types of treatment responses and correlate these findings with patient outcome. Clinical and pathologic parameters from 110 esophagogastrectomies were recorded and analyzed. Two main types of histologic responses were observed: inflammatory-predominant response (59%) and florid foreign body-type giant cell response to keratin (41%). Irrespective of cG, cTNM, and amount of residual cancer, florid foreign body-type giant cell reaction was predominantly noted deep within the esophageal wall, while the inflammatory response was restricted to the mucosa, submucosa, and inner half of muscularis propria. Patients with foreign body-type giant cell response showed significantly better overall survival compared with the inflammatory response group (log-rank test P =0.015). Florid foreign body-type giant cell response was the only factor associated with improved survival in a multivariable analysis for overall survival (hazard ratio=0.5; 95% confidence interval=0.3-1.0; P =0.038), but not in the model for disease-specific survival, whereas ypTNM stage II was the only significant risk factor for disease-specific survival in multivariable analysis (hazard ratio=3.4; 95% confidence interval=1.0-11.2; P =0.047). Our results suggest that in addition to the College of American Pathologists Tumor Regression Score and ypTNM stage, subtype of histologic response to therapy may represent another prognostic marker for neoadjuvantly treated esophageal squamous cell carcinoma.